Learning Vascular and Interventional Radiology - Ribes, Ramón; Muñoz, José J. (Learning Imaging, 2010)
This book is an introduction to interventional radiology. Written in a case-based format, the book is subdivided into ten chapters made up of ten vascular and non-vascular interventional radiology cases.Each case contains illustrations and legends describing the imaging findings and technical details of each intervention, comments from anatomical, physiopathological and radiological standpoints, as well as a description of the interventional procedure and the required interventional devices.The book is aimed at vascular and non-vascular interventional radiologists, vascular surgeons, radiology residents, vascular surgery residents, nurses and radiology technicians. Learning Imaging is a unique case-based series for those in professional education in general and for physicians in particular.